Blood Pressure over Height Ratios: Simple and Accurate Method of Detecting Elevated Blood Pressure in Children - Ovidiu Galescu; Minu George; Sudhakar Basetty; Iuliana Predescu; Anil Mongia; Svetlana Ten; Amrit Bhangoo (Hindawi Limited, 2012)
Background. Blood pressure (BP) percentiles in childhood are assessed according to age, gender, and height. Objective. To create a simple BP/height ratio for both systolic BP (SBP) and diastolic BP (DBP). To study the relationship between BP/height ratios and corresponding BP percentiles in children. Methods. We analyzed data on height and BP from 2006-2007 NHANES data. BP percentiles were calculated for 3775 children. Receiver-operating characteristic (ROC) curve analyses were performed to calculate sensitivity and specificity of BP/height ratios as diagnostic tests for elevated BP (>90%). Correlation analysis was performed between BP percentiles and BP/height ratios. Results. The average age was 12.54 ± 2.67 years. SBP/height and DBP/height ratios strongly correlated with SBP & DBP percentiles in both boys (𝑃<0.001, 𝑅2=0.85, 𝑅2=0.86) and girls (𝑃<0.001, 𝑅2=0.85, 𝑅2=0.90). The cutoffs of SBP/height and DBP/height ratios in boys were ≥0.75 and ≥0.46, respectively; in girls the ratios were ≥0.75 and ≥0.48, respectively with sensitivity and specificity in range of 83-100%. Conclusion. BP/height ratios are simple with high sensitivity and specificity to detect elevated BP in children. These ratios can be easily used in routine medical care of children.